Біологічні особливості шипшини зморшкуватої (Rosa rugosa Thunb.) в умовах інтродукції в Лівобережному Лісостепу України - Kolb, V.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2012)
The results of study of biological peculiarities of Rosa rugosa Thunb. in the conditions of introduction in Left-Bank of Forest-Steppe of Ukraine is given. This species is recommended for including in the assortment for greenery planting of this region.